Sources of Teacher Self-Efficacy in Teaching Phonics to Young Learners - Ryan Andisky Asrul; Sukardi Weda; Fitriyani (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study explores preschool teachers’ self-efficacy in teaching phonics to young learners in a bilingual early childhood setting in Makassar, Indonesia. Although phonics is a widely supported approach to early reading, its application across Indonesian preschools remains inconsistent, especially outside English-based programs. This research aims to examine how teachers perceive their self-efficacy in phonics instruction, identify the factors that shape those beliefs, and understand how these beliefs influence classroom implementation. A descriptive qualitative method was employed, involving three preschool teachers selected through purposeful sampling. Data were collected through semi-structured interviews and classroom observations. The analysis was guided by Bandura’s (1995) four sources of self-efficacy—mastery experiences, vicarious experiences, social persuasion, and emotional states—and Tschannen-Moran and Hoy’s (2001) framework covering instructional strategies, classroom management, and student engagement. Findings revealed that the participants demonstrated high or moderate-to-high self-efficacy in adapting phonics strategies, managing classroom behavior, and engaging students. Mastery experiences, particularly students’ reading progress, were the strongest source of confidence. Other contributing factors included collaboration with peers and encouragement from parents and colleagues. Classroom observations largely confirmed alignment between teachers’ stated beliefs and their instructional practices. The study concludes that teacher self-efficacy significantly affects the quality and consistency of phonics instruction. It recommends that schools support teacher development through reflective practice, peer observation, and accessible teaching resources to improve early literacy outcomes.